Protein quality control at the Golgi. (April 2022) - Schwabl, Sinead; Teis, David
Abstract: The majority of the proteome in eukaryotic cells is targeted to organelles. To maintain protein homeostasis (proteostasis), distinct protein quality control (PQC) machineries operate on organelles, where they detect misfolded proteins, orphaned and mis-localized proteins and selectively target these proteins into different ubiquitin-dependent or -independent degradation pathways. Thereby, PQC prevents proteotoxic effects that would disrupt organelle integrity and cause cellular damage that leads to diseases. Here, we will discuss emerging mechanisms for PQC machineries at the Golgi apparatus, the central station for the sorting and the modification of proteins that traffic to the endo-lysosomal system, or along the secretory pathway to the PM and to the extracellular space. We will focus on Golgi PQC pathways that (1) retrieve misfolded and orphaned proteins from the Golgi back to the endoplasmic reticulum, (2) extract these proteins from Golgi membranes for proteasomal degradation, (3) or selectively target these proteins to lysosomes for degradation.